Differences in Knowledge of Young Women About Early Marriage and Pregnancy at a Young Age Pre and Post Counseling In MAN 4 Kab. Tangerang - Sintha Wijayanti (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Teenage pregnancy occurs between the ages of 14-19 years. The number of those who married early before the age of 18 in 2018 puts Indonesia in the 10 countries with the highest absolute number of child marriages in the world, which is estimated at around 1,220,900. According to the UNFPA report, globally every year it is estimated that 14 million adolescents aged 15-19 years give birth and more than 90% of these births occur in developing countries. This study aims to determine the differences in young women’s knowledge about early marriage and pregnancy at a young age before and after counseling at MAN 4 Kab. Tangerang. This study uses quantitative methods and designs, namely "Quasi-Experimental Non-Equivalent Pretest And Posttest Control Group", the population of this study is the XII grade girls of MAN 4 Tangerang and the sample in this study was 63 respondents. The test used in this research is the T-Test Dependent test which aims to see the differences in the knowledge of young women in pre and post counseling at MAN 4 Kab. Tangerang. The results showed that the significance value was 0.000 < 0.05, then Ho was rejected and Ha was accepted, so counseling about early marriage and early pregnancy provided a difference between pre and post counseling on the knowledge of adolescent girls in class XIII MAN 4 Tangerang. It is hoped that the school will be able to provide a little material related to early marriage and early pregnancy on the sidelines of the subjects that have been determined. For adolescents, this research is expected to bring benefits to knowledge about child marriage and early pregnancy so that adolescents understand the impact of child marriage and early pregnancy.